Long-term follow-up of pallidal deep brain stimulation in two cases of Huntington's disease. Issue 3 (25th October 2010) - Kang, Gail A; Heath, Susan; Rothlind, Johannes; Starr, Philip A
Abstract : Background: Deep brain stimulator (DBS) implantation has been shown to be effective in the treatment of various movement disorders including Parkinson's disease, essential tremor and dystonia. However, there is limited information regarding the potential use of DBS in Huntington's disease (HD). In this study, the authors present their findings on the long-term motor and neurocognitive results of two HD patients (patient 1: 57 years, 42 cytosine-adenine guanine (CAG) repeats; patient 2: 50 years, 41 CAG repeats) who underwent staged bilateral globus pallidus interna DBS surgery. Methods: The patients were evaluated at baseline and at five timepoints throughout a 2-year postoperative during which motoric ratings ((Unified Huntington's Disease Rating Scale), Activities of Daily Living scores (HD-ADL) and neurocognitive testing) were obtained. Results: Both patients had a sustained decline in chorea 2 years after initial DBS surgery. Despite this improvement in chorea, one patient has had continuing deterioration in gait, bradykinesia and dystonia scores, which has caused his ability to perform activities of daily living to return to his baseline level of functioning prior to DBS surgery. Both patients have experienced further gradual decline in neurocognitive functioning, which appears to be independent of DBS and most likely related to disease progression. Conclusion: DBS implantation may be a potential treatment option for a subset of HD patients who have significant functional deficits due to chorea. However, appropriate selection of the best candidates for DBS appears to be challenging, given the difficulty in predicting disease course in HD due to its variable nature.